(untitled) (ItalianoLinguadue, 2011)
Il contributo illustra i risultati di una prima indagine sul livello di penetrazione dell’italiano nell’islandese. Nonostante la sua fama di idioma impermeabile agli influssi stranieri, l’islandese si è rivelato assai aperto alle parole provenienti dalla penisola italiana, sia in passato che nel presente. Oltre ad elencare le parole ritenute dagli studiosi di chiara o ipotetica etimologia italiana, nell‘articolo viene analizzato anche il loro ambito semantico. Italianisms in the icelandic language This paper illustrates the results of an initial survey regarding the level of penetration of Italian in the Icelandic language. Despite it’s fame for being impermeable to foreign influences, Icelandic has adopted words from Italy, in the past and in the present. Besides listing the words which researchers feel are clearly or hypothetically derived from Italian etymology, they are also analyzed semantically.